Changes in Synaptic Proteins Precede Neurodegeneration Markers in Preclinical Alzheimer's Disease Cerebrospinal Fluid - Lleó, Alberto; Núñez-Llaves, Raúl; Alcolea, Daniel; Chiva, Cristina; Balateu-Paños, Daniel; Colom-Cadena, Martí; Gomez-Giro, Gemma; Muñoz, Laia; Querol-Vilaseca, Marta; Pegueroles, Jordi; Rami, Lorena; Lladó, Albert; et al. (Molecular & cellular proteomics, 2019)
In the search for biomarkers of synapse loss associated with Alzheimer's disease (AD), we used shotgun proteomics to identify a panel of 9 synaptic proteins detectable in human cerebrospinal fluid (CSF). Expression at the human synapse was verified using super resolution microscopy. Using SRM, we monitored the panel in CSF from 3 independent clinical cohorts. We report 6 synaptic biomarkers that demonstrate changes in preclinical AD prior to markers of neurodegeneration, which could have clinical value for assessing disease progression. [Display omitted] Highlights •Proteomic analysis of cerebrospinal fluid and identification of synaptic component.•Use of super resolution microscopy to verify synapse-specificity in human tissue.•Selective reaction monitoring MS (SRM) of synaptic panel in 3 cohorts of Alzheimer's disease cerebrospinal fluid.•Synaptic protein changes precede tau in preclinical Alzheimer's disease. A biomarker of synapse loss, an early event in Alzheimer's disease (AD) pathophysiology that precedes neuronal death and symptom onset, would be a much-needed prognostic biomarker. With direct access to the brain interstitial fluid, the cerebrospinal fluid (CSF) is a potential source of synapse-derived proteins. In this study, we aimed to identify and validate novel CSF biomarkers of synapse loss in AD. Discovery: Combining shotgun proteomics of the CSF with an exhaustive search of the literature and public databases, we identified 251 synaptic proteins, from which we selected 22 for further study. Verification: Twelve proteins were discarded because of poor detection by Selected Reaction Monitoring (SRM). We confirmed the specific expression of 9 of the remaining proteins (Calsyntenin-1, GluR2, GluR4, Neurexin-2A, Neurexin-3A, Neuroligin-2, Syntaxin-1B, Thy-1, Vamp-2) at the human synapse using Array Tomography microscopy and biochemical fractionation methods. Exploration: Using SRM, we monitored these 9 synaptic proteins (20 peptides) in a cohort of CSF from cognitively normal controls and subjects in the pre-clinical and clinical AD stages (n = 80). Compared with controls, peptides from 8 proteins were elevated 1.3 to 1.6-fold (p < 0.04) in prodromal AD patients. Validation: Elevated levels of a GluR4 peptide at the prodromal stage were replicated (1.3-fold, p = 0.04) in an independent cohort (n = 60). Moreover, 7 proteins were reduced at preclinical stage 1 (0.6 to 0.8-fold, p < 0.04), a finding that was replicated (0.7 to 0.8-fold, p < 0.05) for 6 proteins in a third cohort (n = 38). In a cross-cohort meta-analysis, 6 synaptic proteins (Calsyntenin-1, GluR4, Neurexin-2A, Neurexin-3A, Syntaxin-1B and Thy-1) were reduced 0.8-fold (p < 0.05) in preclinical AD, changes that precede clinical symptoms and CSF markers of neurodegeneration. Therefore, these proteins could have clinical value for assessing disease progression, especially in preclinical stages of AD.